The Addressability and Impact of Projects Submitted and Financed through Local Action Groups between 2014 and 2020 - Case Study Calarasi County - Rares-Alexandru IONESCU; Emil MUSAT (Communications of International Proceedings, 2020)
For a better understanding on how projects implemented by Local action Groups can contribute to the development of Romanian rural areas, one should start from analyzing the interest shown in submitting projects on sustainable development of rural areas. The present paper analyzes how those local communities from Calarasi, which through the territorial administrative unit are members of a LAG, have responded effectively to local development strategies and measures proposed by them for rural development by modernizing localities, investments in agricultural and non-agriculture activities, supporting entrepreneurship and farmers young generation, as well as through social and cultural investments. By examining the Local Development Strategies and their evaluation, the proposed measures and the submitted projects, it can be seen that, the most interested in accessing the available funds are the public beneficiaries, who submit projects aimed at ensuring public comfort and public safety, ensuring the conditions for recreational activities or improving local social services. If we are to talk about private beneficiaries, it can be highlighted that they have submitted projects late, especially in the agricultural field, and the number of projects is significantly smaller than that of public beneficiaries is at least reluctant. The most accessed areas have been stimulating the development and modernization of localities, followed by the promotion and young farmers support, and also investments in agricultural activities. Main causes for the smaller number of projects submitted by potential private beneficiaries are represented by the lack of knowledge for drafting projects and obtaining the necessary approvals, but also fear of consuming resources without completing the process with the conclusion of a contract.
Keywords: Local Action Groups; Impact; Local Development Strategies.